Digital Marketing and Product Quality on Purchase Interest and Decisions in Industrial Cafés - Melisa Suwardi; Cosmas Gatot Haryono; Fahrul Riza; Irzameingindra Putri Radjamin (CV. AFDIFAL MAJU BERKAH, 2026)
Digitalization has changed the marketing landscape of the food and beverage industry, including in the context of industrial cafes. This study aims to analyze the influence of digital marketing and product quality on purchasing decisions, with purchase intention as a mediating variable. This study answers four main questions: (1) to what extent does digital marketing influence purchase intention, (2) how does product quality influence purchase intention, (3) does purchase intention influence purchasing decisions, and (4) does purchase intention act as a mediator in the relationship between external stimuli and purchasing decisions. This study uses a quantitative approach with Partial Least Squares analysis and PROCESS Macro modeling techniques. The results show that digital marketing and product quality significantly increase purchase intention, with indirect effects of 0.2222 and 0.2257, respectively. Purchase intention was also found to significantly influence purchase decisions (β = 0.347, p < 0.001). Mediation analysis showed that purchase intention acted as a partial mediator. These findings confirm the validity of the Stimulus-Organism-Response (SOR) Model in the consumer behavior of industrial cafes. The researchers suggest that cafe owners integrate attractive digital promotions with product quality improvements to maximize purchase conversion